Nanodiamond photocathodes for MPGD-based single photon detectors at future EIC. (April 2020) - Chatterjee, C.; Cicala, G.; Cicuttin, A.; Ciliberti, P.; Crespo, M.L.; Dalla Torre, S.; Dasgupta, S.; Gregori, M.; Levorato, S.; Menon, G.; Tessarotto, F.; Triloki,; et al.
Abstract: The design of a Ring Imaging CHerenkov (RICH) detector for the identification of high momentum particles at the future Electron Ion Collider (EIC) is extremely challenging by using current technology. Compact collider setups impose to construct RICH with short radiator length, hence limiting the number of generated photons. The number of detected photons can be increased by selecting the far UV region. As standard fused-silica windows is opaque below 165 nm, a windowless RICH can be a possible approach. CsI is widely used photocathode (PC) for photon detection in the far UV range. Due to its hygroscopic nature it is very delicate to handle. In addition, its Quantum Effciency (QE) degrades in high intensity ion fluxes. These are the key reasons to quest for novel PC with sensitivity in the far UV region. Recent development of layers of hydrogenated nanodiamond powders as an alternative PC material and their performance, when coupled to the THick Gaseous Electron Multipliers (THGEM)-based detectors, are the objects of an ongoing R&D. We report here some preliminary results on the initial phase of these studies.